2020
DOI: 10.1002/hpm.3059
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 pandemic and adolescent health and well‐being in sub‐Saharan Africa: Who cares?

Abstract: The health and well-being impact of COVID-19 on global development agendas has wildly been debated. The World Bank has reported that the poor will be hardest hit from the COVID-19 crisis, and that the pandemic could render about 49 million people including children and young people into extreme poverty in 2020. 1 Crucially, lowand middle-income countries (LMICs) would be greatly affected with almost half of the projected new poor (23 million) been in sub-Saharan Africa. 1 Sub-Saharan Africa again bears the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 4 publications
1
25
0
1
Order By: Relevance
“…11 In addition to the direct loss of formal education, the critical social protective functions of schools are lost with school closure, which may result in increased child labor, early marriages, adolescent pregnancies, transactional sex, genderbased violence, mental health issues, or exposures to risky behaviors such as tobacco smoking and drug use. 13,[28][29][30][31][32][33] Recently, a survey in Kampala, Uganda, reported that COVID-19 lockdowns were associated with a higher prevalence of unhealthy behaviors such as tobacco smoking/chewing, alcohol drinking, and substance use (such as marijuana). 14 Due to the increased risks of such issues and the direct deprivation of educational opportunities, many adolescents in SSA may not go back to school even after schools reopen after a crisis like the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In addition to the direct loss of formal education, the critical social protective functions of schools are lost with school closure, which may result in increased child labor, early marriages, adolescent pregnancies, transactional sex, genderbased violence, mental health issues, or exposures to risky behaviors such as tobacco smoking and drug use. 13,[28][29][30][31][32][33] Recently, a survey in Kampala, Uganda, reported that COVID-19 lockdowns were associated with a higher prevalence of unhealthy behaviors such as tobacco smoking/chewing, alcohol drinking, and substance use (such as marijuana). 14 Due to the increased risks of such issues and the direct deprivation of educational opportunities, many adolescents in SSA may not go back to school even after schools reopen after a crisis like the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, the public health measures put in place to combat the pandemic, such as extended self-isolation and physical distancing, lockdowns of communities, and the closures of schools, may have adverse collateral effects on the development and health of adolescents that may be difficult to reverse. [11][12][13] In addition to the direct losses of educational opportunities due to school closures, school-based nutrition programs, such as school feeding and nutrition education, are also disrupted by the pandemic. A recent cross-sectional study in Kampala, Uganda, reports that COVID-19 lockdowns led to mental health challenges, reduced ability to meet basic needs, disruptions to socioeconomic status, and engagement in unhealthy behaviors among adolescent boys and young men.…”
Section: Introductionmentioning
confidence: 99%
“…Despite calls to continue the provision of a minimum package of SRH care during the COVID-19 pandemic, 1, 18,19 what happened during the 2014-16 outbreak of Ebola virus disease in west Africa is instructive. 20 In Sierra Leone adolescents had reduced capability to access or use SRH services during the Ebola outbreak, and cash-strapped health services diverted resources away from essential SRH services to acute responses that facilitated Ebola containment.…”
mentioning
confidence: 99%
“…21 Consequently, it is likely that during the COVID-19 pandemic the compounding effects of limited access to SRH services, isolation, and loss of family members and income have disproportionately affected adolescent girls and young women, further exacerbating gender inequalities and GBV. 1,18 It will be some months before the impacts of COVID-19 on adolescent girls and young women will be fully appreciated, including the social harms and inadvertent negative outcomes of the COVID-19 response. A risk-benefit assessment is needed to identify and mitigate the indirect effects of COVID-19 mitigation and containment strategies to address these impacts and also to prepare for the next epidemic.…”
mentioning
confidence: 99%
“…Few data are available on the knowledge of COVID-19 among adolescents and youths, especially in African countries [ 16 ]. At-risk populations’ demographic characteristics play a vital role in the type and intensity of measures necessary to curb the spread of the virus.…”
Section: Discussionmentioning
confidence: 99%